A GRAMMATICAL ANALYSIS ON ENGLISH BLOG POSTING OF STUDENTS ENGLISH LANGUAGE TEACHING DEPARTEMENT STATE ISLAMIC COLLEGE JURAI SIWO METRO 2012/2013 - Mifarizki, Ady (Department of English Education of STAIN Jurai Siwo Metro, 2014)
Nowadays, the advanced technology widely makes different ways to learn English grammar. This study is aimed to analyze academic writing via blog posting in grammatical aspects. It is involved 11 students of English Language Teaching Department which have 18 articles published on English blog. Therefore, the data were collected through observation and documentation by Creswellâs model. To display all of the results the writer used chart in grammatical analysis. The result of this study had been classified into four common errors, namely concord with 47% error items, word order with 33% error items, spelling with 14% error items, and parallel structure with 6% error items. The result of the study can encourage the students to pay big attention to grammatical aspects of writing